The Educational implications of Biological Crises at the Governmental and Popular Levels:Corona: Covid-19 Crisis as a Model - Fadi Abdalkareem Alrababah; Hilda Ahmad E'layan Elbashabsheh (Deanship of Scientific Research (DSR), the University of Jordan, 2024)
Objectives: The study aimed to demonstrate the educational implications of biological crises at the governmental and popular levels which were represented by the crisis (Corona Covid-19) as a model. Methods: The research followed the inductive, descriptive approach to determine the educational repercussions of the Corona crisis. The research benefited from official reports issued by the competent authorities through their official websites and reference to a number of studies that reinforce the current study in some of its aspects. Results: The study found that there are many educational implications of biological crises at the governmental, popular, national and international levels. These implications examined by the study were (41) repercussions; (25) at the governmental level and (16) at the popular level, some of which are positive, while others are negative to enhance and improve the positive impact, and avoid the negative one. Conclusions: The study reported many educational repercussions of biological crises at the governmental and popular levels, which emerged through practical practices during the Corona crisis, because knowing these repercussions contributes to assisting the competent authorities, citizens, and educational institutions in drawing up policies and future strategic plans and developing appropriate procedures in managing similar crises in human.